Male teachers in preschool teaching levels – a feminist Viewpoint - Alharahsheh, Husam; Pius , Abraham; Guenane , Imad (Advances in Social Sciences Research Journal, 2021)
Abstract: The aim of this brief paper is to explore and demonstrate the importance of teacher’s gender at the preschool levels of education and would be focussing on men as professional teachers at the preschool level of education or nursery level of education, and how the participation of male teachers has contributed to the feminist view within teaching. The paper is primarily supported by secondary research through inclusion and consideration of different peer reviewed academic papers relating to the subject. The paper highlights key considerations and reasons derived from different countries in relation to the underrepresentation of males within this level of education including low salaries, dominance of female’s numbers in the profession, the negative stigma associated with men working within this level of education, and social fears. However, male presence in this level of education is supported due to various reasons including diversification of students’ experience within preschool levels of education and consideration of equality matters.